Seizures and risk of epilepsy in autoimmune and other inflammatory encephalitis - Spatola, M. (Curr Opin Neurol, 2017)
PURPOSE OF REVIEW: To assess the seizure manifestations and risk of epilepsy in encephalitis associated to antibodies against neuronal cell-surface (AE) or myelin-associated antigens, and to review several chronic epileptic disorders including, Rasmussen’s encephalitis (RE), fever-induced refractory epileptic syndromes (FIRES), and new-onset refractory status epilepticus (NORSE). RECENT FINDINGS: Seizures are a frequent manifestation of AE. Some AE may associate with characteristic features: faciobrachial dystonic seizures (anti-LGI1 encephalitis), EEG extreme delta brush (anti-NMDAR), or multifocal FLAIR-MRI abnormalities (anti-GABA(A)R). In anti-LGI1 encephalitis, cortical, limbic, and basal ganglia dysfunction results in different types of seizures. AE or myelin-antibody associated syndromes are often immunotherapy-responsive and appear to have a low risk for chronic epilepsy. In contrast patients with seizures related to GAD65-antibodies (an intracellular antigen) frequently develop epilepsy and have suboptimal response to treatment (including surgery). RE or FIRES may occur with autoantibodies of unclear significance and rarely respond to immunotherapy. A study of patients with NORSE showed that 30% developed chronic epilepsy. SUMMARY: Although seizures are frequent in all types of AE, the risk for chronic epilepsy is dependent on the antigen: lower if located on the cell-surface, and higher if intracellular. For other disorders (RE, FIRES, NORSE) the prognosis remains poor.